Including credibility and expertise in group decision-making process: an approach designed for UbiGDSS - Carneiro, João (2017)
Supporting group decision-making when the decision-makers are spread around the world is a complex process. The mechanisms of automated negotiation, such as argumentation, can be used in Ubiquitous Group Decision Support Systems to help decision-makers find a solution based on their preferences. However, there are some other important issues that affect the decisionmaking process beyond typical preferences over criteria and alternatives. In this paper, we propose an algorithm that will allow agents to reason about self-expertise and other decision makers’ credibility. This way, we intend agents to achieve better quality and more consensual decisions. Our algorithm includes not only the decision-maker’s preferences but also his intentions in the process. By using the proposed model, agents achieved a stronger consensus in all scenarios that were considered and higher satisfaction levels in the most complex scenarios.